2022
DOI: 10.1088/1755-1315/997/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Reporting and Corporate Governance among Asian and African Energy Firms

Abstract: This paper examines the extent of climate change disclosure among energy firms operating in Africa and Asia, as well as the firm, country and global determinants of the disclosures. A quantitative approach was applied to evaluate an unbalanced panel data of 31 firms in 18 countries across Africa and Asia for 2015 to 2020. Data was collected from the GRI database and a composite index was constructed to measure the extent of climate change disclosure using “GRI 305: Emissions” indicators. The study used a regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…The finding is aligned with the work of previous scholars and the resource dependency theory, which indicate that having women board members enhances a firm's tendency to report carbon-related disclosures. This study found that there is a positive relationship between women's leadership and their bringing of resources to the company and environmental disclosure [33,[87][88][89][91][92][93][94][95][96]144,[150][151][152][153][154][155][156][157][158][159][160][161]. On the other hands, even though this research has a similar scope of study to previous work, it is significantly different from prior scholars' findings, who have found that carbon-related disclosure and women's leadership were specifically investigated.…”
Section: Conclusion and Recommendationscontrasting
confidence: 87%
“…The finding is aligned with the work of previous scholars and the resource dependency theory, which indicate that having women board members enhances a firm's tendency to report carbon-related disclosures. This study found that there is a positive relationship between women's leadership and their bringing of resources to the company and environmental disclosure [33,[87][88][89][91][92][93][94][95][96]144,[150][151][152][153][154][155][156][157][158][159][160][161]. On the other hands, even though this research has a similar scope of study to previous work, it is significantly different from prior scholars' findings, who have found that carbon-related disclosure and women's leadership were specifically investigated.…”
Section: Conclusion and Recommendationscontrasting
confidence: 87%
“…Investment banks such as Goldman Sachs and JPMorgan play a crucial role in providing financial advisory services, including capital structuring, mergers and acquisitions, and risk management (Chaudhry et al, 2021). Specialized energy advisory firms like Wood Mackenzie and IHS Markit focus on providing industry-specific insights, market intelligence, and strategic advice, enabling petroleum companies to make informed decisions in a rapidly evolving energy landscape (Amegatcher et al, 2022). Additionally, publicly funded business advisory services offer specific advice tailored to the challenges unique to specific firms in the petroleum industry (Cumming et al, 2014).…”
Section: Corporate Social Responsibility (Csr) In the Petroleum Industrymentioning
confidence: 99%
“…A substantial minority of them share the results of empirical research on corporate climate-related disclosures; only twenty one present various types of indices measuring the level of climate-related disclosures by companies, nine of which focus on GHG emissions (e.g. Asare et al, 2022;Ika et al, 2022;Wedari et al, 2021), five employ the CDP methodology (e.g. de Grosbois & Fennell, 2022;Ika et al, 2022;Charumathi & Rahman, 2019), two resorted to the TCFD methodology (Amar et al, 2022;Demaria & Rigot, 2021).…”
Section: An Overview Of the Literaturementioning
confidence: 99%